Frontier progress and translational challenges of pluripotent differentiation of stem cells - Su, Zhengbing; Dong, Hui; Fang, Xiang; Zhang, Wenli; Duan, Hong (Frontiers in Genetics, 2025)
Stem cell research has significantly transformed regenerative medicine, with pluripotent stem cells (PSCs) serving as the cornerstone for disease modeling, drug screening, and therapeutic applications. Embryonic stem cells (ESCs) exhibit unparalleled self-renewal and tri-lineage differentiation, while induced pluripotent stem cells (iPSCs) bypass ethical constraints through somatic cell reprogramming. Clinical trials highlight the potential of mesenchymal stem cells (MSCs) in osteoarthritis and graft-versus-host disease, which leverage their immunomodulatory and paracrine effects. Despite advancements, challenges persist: iPSCs face epigenetic instability and tumorigenic risks, and adult stem cells struggle with inefficient differentiation. This paper systematically reviews stem cell source classification, differentiation regulatory mechanisms, cutting-edge technologies such as CRISPR/Cas9, and explores field-specific controversies (e.g., epigenetic stability of iPSCs) and future directions (e.g., integration of organoids and biomaterials). By analyzing current progress and challenges, it provides a multidimensional perspective for stem cell research.